Systematic Literature Review: Customer Satisfaction With Mobile Banking Super Apps - Rinda Hesti Kusumaningtyas; Aliza Fatha Amanda; Safina Yulianti; Sultan Tedja Permana (Komunitas Dosen Indonesia, 2025)
The rapid growth of digital banking has transformed customer interaction patterns, leading Islamic financial institutions to develop mobile banking super apps that integrate financial and lifestyle services. However, research comparing customer satisfaction across multiple Islamic super apps remains limited. This study aims to systematically examine and synthesize previous research on user satisfaction factors and analytical approaches used in Islamic mobile banking applications in Indonesia, focusing on BYOND by BSI, Muamalat DIN, and Mobile Maslahah. This research adopts the Systematic Literature Review (SLR) method following the frameworks of Kitchenham (2004) and Petersen et al. (2008). Relevant peer-reviewed articles published between 2021 and 2025 were retrieved from academic databases such as Google Scholar, ResearchGate, and SINTA. The inclusion criteria ensured that only studies explicitly addressing customer satisfaction with Islamic mobile banking were analyzed. Fifteen studies met the inclusion requirements and were synthesized through narrative and thematic analysis. The findings reveal that most studies applied quantitative descriptive approaches, with Technology Acceptance Model (TAM) as the most commonly used framework. Key satisfaction determinants include ease of use, efficiency, trust, service quality, and Sharia compliance. These indicate that both functional performance and Islamic value alignment play crucial roles in shaping customer satisfaction. The review contributes to the literature by highlighting comparative satisfaction patterns among Islamic super apps and identifying research gaps for future empirical validation. Recommendations are offered for banks and developers to enhance user experience while reinforcing Sharia-based trust.